Intellectual capital disclosure in annual reports of Islamic banks: a comparative study of Malaysia and Indonesia - Suarni, Agusdiwana (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
This study focuses on four specific objectives. Firstly, the study examines the extent and quality of the Intellectual Capital Disclosure (ICD) in the annual reports of Malaysian and Indonesian Islamic banks from 2009 until 2013. Secondly, it aims to examine the categories of ICD (extent and quality) in both Malaysian and Indonesian Islamic banks over time. Thirdly, this study also focuses on the comparison of the ICD of Malaysian and Indonesian Islamic banks during the study period of five years. Fourthly, the study determines the factors that influence the ICD in the annual reports of Malaysian and Indonesian Islamic banks. The study adopted the quantitative research method. The extent of disclosure was measured by applying a checklist of 33 items. Differences in the extent of disclosure between the two countries were assessed by using independent sample t-test. Multiple regression analysis was performed to determine the factors that influence disclosure of IC. The data are from the annual reports on the websites of Islamic banks in Indonesia and Malaysia over five years from 2009 to 2013. The total sample of this study is 122 annual reports from these two countries. The results showed that the trend of ICD in the annual reports of Malaysian and Indonesian Islamic banks increased over the five years. In addition, the empirical results indicated that, for both countries the highest disclosure was for external capital, while the lowest was for human capital. Furthermore, Indonesian Islamic banks have a higher ICD compared to Malaysian Islamic banks. In addition, based on the multivariate regression results of determinants, the number of members with experience on other Shari'ah Committees (SC) has a significant positive effect on the extent of ICD (i.e. overall) in the annual reports of Malaysian Islamic banks, while the numbers of SC has a significant negative association with the quality of ICD in Indonesian Islamic banks. In addition, board size, leverage and ROE have significant positive influence on the quality of ICD in Indonesian Islamic banks. Thus, this study provides several contributions to the study area of ICD. Firstly, it is beneficial for stakeholders to invest their money in banks with higher ICD. Secondly, it helps to identify the trend of Malaysian and Indonesian Islamic banks to encourage the accounting regulators to pay more attention to ICD and simultaneously, it can be helpful for other users to understand the components of IC in Islamic banks. Thirdly, this study focuses on comparison between Indonesian and Malaysian Islamic banks; therefore, this study depicts a picture of which country has better ICD in the annual reports of Islamic banks. Regulation should take these findings into consideration, particularly on the effects on attracting investors, since both Malaysia and Indonesia aim to be Islamic financial hubs.